Association of sudden in-hospital cardiac arrest with emergency department crowding. (May 2019) - Chang, Yu-Hsin; Shih, Hong-Mo; Chen, Chih-Yu; Chen, Wei-Kung; Huang, Fen-Wei; Muo, Chih-Hsin
Abstract: Background: In Taiwan, emergency department (ED) crowding is inevitable; many studies have investigated the various negative effects of ER crowding on patients. In general, ED crowding reduces patient satisfaction, delays treatment, and increases mortality. However, most studies have focused on the relationship between ED crowding and delay mortality rather than sudden mortality. This study investigates the association of ED crowding with sudden unexpected in-hospital cardiac arrest (IHCA). Methods: The retrospective observational study recruited patients with sudden IHCA in an ED from February 2016 to September 2017. Exclusion criteria included (1) out-of-hospital cardiac arrest, (2) patient with signed do-not-resuscitate consent, (3) pediatric patient, and (4) trauma patient. ED crowding parameters, including ED bed occupancy rates (EDBORs), number of boarding patients, and patients with boarding time to general ward or intensive care unit of >24 and >48 h, all were recorded every 2 h. Results: Significant increments were noted in IHCA incidence when EDBOR was >260%, with a rate ratio of 1.50 (95% confidence interval [CI], 1.03–2.17). However, the number of boarding patients was not associated with IHCA incidence (P > 0.05). Prolonged boarding time to general ward and ICU of >24 and >48 h both increased the IHCA incidence. Conclusion: This first study investigating the relationship between ED crowding and sudden IHCA found EDBORs and prolonged boarding to general wards or ICUs were associated with increased sudden IHCA incidence.